(untitled) (KASBIT Business Journal, 2022)
One of the crucial and fastest growing areas of criminal activity is cybercrime. Most of the small businesses do not have the financial and technological means to protect their systems from cyber-attacks, leaving them vulnerable to data breaches. This study aims to explore this issue using case study method based on examination of cyber security strategies employed at small business. Primary data is collected through an on-line survey from (50 business companies) and semi-structured interviews. Using the first stage of grounded ontology methodology, the result show that the small businesses should utilize the managed cybersecurity services offered by experts as an outsourced service and that cybersecurity awareness among the users must be diligently promoted since the humans are the weakest link. These recommendations should be useful for the small businesses.